Pendampingan Kampanye Sekolah Sehat pada Guru dan Siswa di Lingkungan Sekolah Dasar Negeri Kabupaten Bandung: Healthy School Campaign Assistance to Teachers and Students in Elementary School, Bandung Regency - Alfin, Riandi; Widianti, Anggriyana Tri; Gartika, Nina; Fauziah S, Alifah; Maulana, Ridwan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
School is a formal institution, where students receive education and lessons given by teachers. In advancing national development, children invest in development in the field of labor and heirs of the country in the future, so guidance for children needs to start early. In this regard, the fields of education and health play a major role because schools are organisationally under the Ministry of National Education, while the Ministry of Health is functionally responsible for the health of students. The Ministry of Education and Culture launched the Healthy School Campaign (KSS) with the theme ‘Healthy School’ by focusing on 3 Health, namely (1) Healthy Nutrition, (2) Healthy Physical, and (3) Healthy Immunisation. The purpose of this community service is to assist the Healthy School Campaign for teachers and students at SDN, Bandung Regency. The method used is action review. The main targets of this community service activity are 25 teachers and 75 students in grades 3, 4, and 5. The results obtained are programs that support healthy school campaigns, namely in the aspects of healthy nutrition, physical health, and healthy immunization. As for after being given health education, there is an increase in the number of students who have very good knowledge (65.3) and students who have good behavior (97.4). Education about PHBS needs to be prioritised in curricular and extracurricular activities, by actively involving students in hygiene and health activities.